The Effect of Sharia Monetary Instruments on the Profitability of Sharia Commercial Banks in Indonesia in 2019-2023 - Ramadhan, Mohammad Ali; Masrifah, Atika Rukminastiti (EQUILIBRIUM, 2024)
The purpose of this study is to evaluate the impact of Sharia Interbank Money Market (PUAS), Sharia Bank Indonesia Facility (FASBIS), and Sukuk Bank Indonesia (SukBI) on Return On Assets (ROA) of Indonesian Islamic Commercial Banks. This research uses a quantitative deductive approach using EViews 10 test tools and VAR / VECM techniques. This study uses secondary data with time series data from January 2019 to November 2023. The dependent variable in this analysis is ROA, while the independent variables are SukBI, FASBIS, and PUAS. Based on the research findings, over time, the SukBI variable significantly reduces the return on assets (ROA) of Indonesian ShariaCommercial Banks; on the contrary, the FASBIS variable has no significant effect on ROA, and the PUAS variable has no significant effect on ROA. The SukBI and FASBIS factors did not have a significant short-term impact on the ROA of Indonesian Islamic Commercial Banks. Meanwhile, the ROA of Indonesian Islamic Commercial Banks is significantly negatively affected by PUAS.